Acute Myocarditis in a young infant: a case reflection - Anuar, Muhamad Azamin; Abu Bakar, Asrar; Abdul Rahman, Amir Hamzah; Hasan, Taufiq Hidayat; Mohamed, Mossad Abdelhak Shaban (2019)
Introduction: In Malaysia, a course of vaccination DTaP/IPV/Hib was introduced in 2008, replacing the 2006 DwPT-HBV/Hib+OPV vaccines. Severe systemic adverse reactions after diphtheria, tetanus and pertussis vaccination are uncommon. Cardiac complications are rarely reported and is most probably implicated to the pertussis component. We describe a rare case of acute myocarditis that developed 60 hours after DTaP/IPV/Hib vaccination.